Optimized harmonic PWM implementation in a reduced switch count MLI with quadruple boosting using PSO for solar PV applications - Ahmad, Salman; Ahmad, Jahangeer; Bakhsh, Farhad Ilahi (Engineering Research Express, 2025)
The reduced switch multilevel inverters are used in many applications specially in renewable energy system. They have a smaller number of semiconductor devices, complexity and thus lower cost and power losses. A reduced-switch multilevel inverters (MLIs) with quadruple boosting capability have been investigated in this study by implementing an optimized harmonic pulse width modulation (OPWM) technique. As an example, a nine-level quadruple boosting inverter, operating at fundamental frequency, is analysed to reduce the dominant lower order harmonics such as third, fifth, and seventh-order harmonics in the output voltage along with control on fundamental component. The particle swarm optimization (PSO) algorithm is employed to obtain the optimize the switching angles using a constrained nonlinear objective function. The computational results have been used to simulate the nine-level quadruple boost inverter and results shows a significant reduction in lower order harmonics. The simulation results have been verified on a prototype of nine-level quadruple boost inverter.